Handbook for Filipinos overseas - Philippines. Commission on Filipinos Overseas (Manila Commission on Filipinos Overseas, 2002)
Gives information on a broad array of government guidelines, policies, programs, and activities of the Philippines about Filipinos overseas and Foreign Affairs. Provides procedures on getting the requirements on working abroad, filing immigration papers, and the benefits of retirement of Overseas Filipino workers.
Keywords: Filipinos -- Employment -- Government policy. -- Foreign countries; Filipinos -- Employment -- Foreign countries -- Handbooks, manuals, etc; Manpower policy -- Philippines